AI-Driven Blood Glucose Management: Integrating Predictive Analytics with Continuous Monitoring Systems - Phani Kumar Praturi, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents an advanced framework for integrating predictive and adaptive analytics with continuous glucose monitoring (CGM) systems to enhance diabetes management. The proposed approach combines real-time CGM data with sophisticated deep learning algorithms, specifically utilizing Long Short-Term Memory (LSTM) networks and attention mechanisms to forecast glucose trends and provide personalized interventions. By implementing a dynamic feedback loop incorporating patient-specific factors such as dietary patterns, physical activity, and medication adherence, the system continuously refines its recommendations through adaptive learning algorithms to optimize treatment outcomes. The mathematical foundation includes specialized loss functions combining Mean Squared Error, Clarke Error Grid Analysis, and Time in Range optimization, ensuring both clinical relevance and prediction accuracy. The system's architecture addresses key challenges in current diabetes care through multi-headed attention mechanisms and hierarchical feature processing, enabling proactive intervention and personalized treatment adaptation. Implementation results demonstrate significant improvements in glycemic control, treatment adherence, and patient engagement while reducing adverse events through early prediction capabilities. This integrated approach, supported by comprehensive mathematical modeling and robust technical infrastructure, significantly advances automated diabetes management. The framework offers healthcare providers and patients a powerful, theoretically grounded tool for optimizing treatment strategies and improving long-term health outcomes. The article also addresses implementation challenges, including data privacy considerations, algorithm bias mitigation, and system integration requirements, providing insights for future developments in AI-driven diabetes care.
Keywords: continuous glucose monitoring; artificial intelligence; predictive analytics; diabetes management; adaptive algorithms